2011
DOI: 10.1097/dcr.0b013e31821d37a3
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneity of KRAS Status May Explain the Subset of Discordant KRAS Status Between Primary and Metastatic Colorectal Cancer

Abstract: KRAS status in a primary site may be used for selecting patients who would benefit from anti-epidermal growth factor receptor therapy. However, KRAS status can be heterogeneous within a primary tumor, and thus different parts of such tumors should be examined for KRAS status to correctly predict the KRAS status in metastatic lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
53
0
1

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 72 publications
(61 citation statements)
references
References 39 publications
7
53
0
1
Order By: Relevance
“…Potential reasons to explain this phenomenon are the intratumoral heterogeneity of KRAS alleles within individual primary CRCs (18) and the discordant KRAS status between primary tumor and corresponding metastases (19,20). It has also been reported that the intratumoral heterogeneity within a primary CRC can explain the discordant KRAS status between primary and metastatic CRC tumors (21). In addition, mutational testing requires tumor tissue samples resected by biopsy or surgery, but samples from metastatic tumors are uncommon because of the difficulty of accessing them and low tumor content secondary to treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…Potential reasons to explain this phenomenon are the intratumoral heterogeneity of KRAS alleles within individual primary CRCs (18) and the discordant KRAS status between primary tumor and corresponding metastases (19,20). It has also been reported that the intratumoral heterogeneity within a primary CRC can explain the discordant KRAS status between primary and metastatic CRC tumors (21). In addition, mutational testing requires tumor tissue samples resected by biopsy or surgery, but samples from metastatic tumors are uncommon because of the difficulty of accessing them and low tumor content secondary to treatment effect.…”
Section: Discussionmentioning
confidence: 99%
“…This may be due to heterogeneity of the primary tumor. If different parts of the primary tumor are examined, the false-negative rate could be abrogated [92].…”
Section: Krasmentioning
confidence: 99%
“…We reported that, as KRAS mutations in some primary tumors are heterogeneous, there are 10% of cases in which KRAS gene status between the primary tumor and metastatic tumors in the same patient are different (30). There were studies reporting a high KRAS gene concordance rate of 95% or more (31 -33) between primary and metastatic tumors.…”
Section: Kras Mutational Status In Japanese Patientsmentioning
confidence: 99%